Introduction to information systems - Rainer, R. Kelly (Rex Kelly); Cegielski, Casey G. (Wiley, 2013)
Information technology professionals will gain invaluable information with this updated resource on how to connect concepts to key business areas. These areas include accounting, finance, marketing, management, human resources, and operations.